2019
DOI: 10.1039/c9bm00749k
|View full text |Cite
|
Sign up to set email alerts
|

A dual-enzymatically cross-linked injectable gelatin hydrogel loaded with BMSC improves neurological function recovery of traumatic brain injury in rats

Abstract: BMSC-laden gelatin hydrogels dual-enzymatically cross-linked by GOX and HRP could significantly promote the neurological function recovery of TBI in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…An increasing number of studies have demonstrated MSC-derived exosomes (MSC-exos) have innate therapeutic potential by virtue of their intrinsic cargoes. MSCexos have shown excellent efficacy in tissue repair and regeneration of many organs, including liver, lung, cartilage, myocardium, brain, spinal cord, and kidney [15][16][17][18][19][20][21][22]. Taking acute kidney injury (AKI) as an example, MSC-exos exert a series of renoprotective and regenerative effects through various mechanisms, including anti-inflammatory, immunomodulatory, anti-necroptosis, anti-apoptosis, and promoting cell proliferation [15,23].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated MSC-derived exosomes (MSC-exos) have innate therapeutic potential by virtue of their intrinsic cargoes. MSCexos have shown excellent efficacy in tissue repair and regeneration of many organs, including liver, lung, cartilage, myocardium, brain, spinal cord, and kidney [15][16][17][18][19][20][21][22]. Taking acute kidney injury (AKI) as an example, MSC-exos exert a series of renoprotective and regenerative effects through various mechanisms, including anti-inflammatory, immunomodulatory, anti-necroptosis, anti-apoptosis, and promoting cell proliferation [15,23].…”
Section: Introductionmentioning
confidence: 99%
“…The grafting of phenol groups onto gelatin was analyzed by the 1 H NMR and UV‐vis spectra of gelatin and GH polymer (Figure S1a, b). The results clearly presented that the integration value corresponding to phenol groups (6.7–7.1 ppm and 275 nm) of GH was much higher than that of gelatin, confirming the successful conjugation of HPA to the gelatin backbones (Lee et al, 2014; Yao et al, 2019c). Additionally, the phenolic contents of these gelatin derivatives reached 23.27 μmol in 1 g of GH determined by the standard curve of HPA (Figure S1c).…”
Section: Resultsmentioning
confidence: 63%
“…Injectable hydrogels are highly suitable for the treatment of TBI [ 1 , 14 , 15 ], since its injection can minimize the damage to the skull and ensure the direct access of its-carried medicine to the lesion [ 16 ]. In addition, hydrogels can be carriers for various bioactive elements, such as stem cells, cytokines and drugs.…”
Section: Introductionmentioning
confidence: 99%